Use of mobiles in dairying for information dissemination: A multi-stakeholder analysis in India - RATHOD, PRAKASHKUMAR; CHANDER, MAHESH; BANGAR, YOGESH (The Indian Journal of Animal Sciences, 2016)
Among all the information and communication technology (ICT) tools, mobile phone has emerged as one of the widely accepted and adopted instruments for delivery of agriculture and livestock related information. Though, mobile use in dairying is considered as an emerging tool in Indian dairy industry, there is a need to study its impact at field conditions. With this theoretical background, the study has focused on the efforts of government of India for mobile message delivery, perception and per cent gap among multi-stakeholders with regards to relevance, profitability and sustainability of mobile use in dairying. The study included primary data using 360 dairy farmers, 80 research scientists and 40 extensionists in North India and also relevant secondary data. The study revealed that perception of scientists and extension experts was more favorable towards relevance, profitability and sustainability of mobile use in dairying, while the perception of farmers was less favourable towards mobile use. The study also observed that there was a wide gap (higher per cent gap) among farmers-scientists and farmers-extensionists withn regards to relevance, profitability and sustainability, while the gap was very narrow among scientists and extensionists. The study concluded that researchers and extension experts need to be familiarized about use of mobiles to disseminate information and improve productivity in the dairy sector. Further, the scientists have to generate and transfer field relevant, profitable and sustainable tools and techniques with the involvement of farmers as the partners of research and extension for effective generation and transfer of dairy innovations.